Ramsay Hunt syndrome in a child – case report - Grabowska, Joanna; Ankudowicz, Anna; Ankudowicz, Grzegorz K. (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction. Ramsay Hunt syndrome is a rare disease characterized by complications of herpes zoster oticus. This syndrome is defined by characteristic skin lesions with paresis of the facial and/or vestibulocochlear nerve. Objective. To present a case of a 14-year-old child with Ramsay Hunt syndrome. Case report . A 14-year-old patient was admitted to the Department of Dermatology due to vesicular lesions in the left auricular region. On medical examination, insufficiency of the left eyelid, asymmetry of the facial lines, drooping of the left corner of the mouth, and smoothing of the forehead were observed. According to the House-Brackmann scale, the patient had paresis (grade IV) of the facial nerve. The patient was treated with intravenous acyclovir, antibiotics and anti-inflammatory drugs. Supplementation with vitamin B and rehabilitation procedures were also introduced. Conclusions . Ramsay Hunt syndrome is very rare in the pediatric population. It requires interdisciplinary cooperation between doctors. The presented case confirms the validity of therapy with acyclovir and prednisone and rehabilitation.